Analysis of Competence and Facilitation Skills of Novice Environmental Guides in Facilitating Catechesis of the Faithful in St. Peter Chrysologus Parish Semarang - Dewi Ratna Jai; Hartutik Hartutik Hartutik; Timotius Tote Jelahu (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2025)
Community catechesis represents a model of faith education that emphasizes active community participation in living out the faith. However, the effectiveness of catechesis greatly depends on the competence and facilitation skills of environmental guides, especially those who are still novices. This study highlights the gap between theological understanding and facilitation practice that remains a challenge in building a dialogical and transformative learning process. This research aims to analyze the competence and facilitation skills of novice environmental guides in community catechesis at St. Peter Chrysologus Parish BSB. Using a qualitative approach, this research employs in-depth interviews and thematic analysis of eight key informants, including the parish priest, senior environmental guides, novices, and members of the catechetical commission. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña to identify patterns of required competencies and skills (Bazeley 2020). The results show that the basic competencies of environmental guides include a strong foundation of faith, doctrinal understanding, and the ability to manage group dynamics. However, they still face challenges in facilitating reflective dialogue and creating active participant engagement. Effective facilitation skills, such as active listening, creating safe spaces, and summarizing discussions, become key factors in improving the quality of catechesis. This research contributes to the development of more comprehensive training strategies for novice environmental guides, emphasizing experience-based approaches, mentoring, and continuous evaluation. The practical implications of this research point to the need for reform in catechetical training to address regeneration challenges and improve facilitation effectiveness in Church base communities.